2022
DOI: 10.1186/s12981-022-00461-4
|View full text |Cite
|
Sign up to set email alerts
|

What is polypharmacy in people living with HIV/AIDS? A systematic review

Abstract: Polypharmacy in people living with HIV/AIDS (PLWHA) is a rising morbidity that exacts hefty economic burden on health budgets in addition to other adverse clinical outcomes. Despite recent advances, uncertainty remains around its exact definition in PLWHA. In this systematic review and Meta-analysis, we explored relevant databases (PUBMED, EMBASE, CROI) for studies evaluating polypharmacy in PLWHA from January 2000 to August 2021 to ascertain the exact numerical threshold that defines this morbidity. Two indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…[4,[19][20][21] Data from pharmaco-epidemiological studies in patients with alternative morbidities, such as people living with HIV/AIDS, have shown that among the factors that drive adverse consequences of polypharmacy include the inherent propensity of parent antiretroviral drugs to bidirectional interactions, as well as the metabolizing pathways of some of the antiretroviral drugs which are highly polymorphic and therefore prone to pharmacogenetic interactions. [22][23][24] In patients with CLD it is unlikely that the nature of underlying primary liver pathology will significantly alter the prevalence estimates of polypharmacy; as previous studies have shown that very often what principally drives the medication count in these cohorts of patients has been the rising number of drugs prescribed to manage, sometimes, inevitable complications (such as portal hypertension and its sequelae, sub-acute bacterial peritonitis, and portal hypertensive gastropathy, etc) that accompany decompensation in these patients. [5,25] However, devising intervention strategies aimed at both the identification and reduction of the risks and consequences of polypharmacy in this vulnerable population will require an unambiguous risk-stratification tool.…”
Section: Discussionmentioning
confidence: 99%
“…[4,[19][20][21] Data from pharmaco-epidemiological studies in patients with alternative morbidities, such as people living with HIV/AIDS, have shown that among the factors that drive adverse consequences of polypharmacy include the inherent propensity of parent antiretroviral drugs to bidirectional interactions, as well as the metabolizing pathways of some of the antiretroviral drugs which are highly polymorphic and therefore prone to pharmacogenetic interactions. [22][23][24] In patients with CLD it is unlikely that the nature of underlying primary liver pathology will significantly alter the prevalence estimates of polypharmacy; as previous studies have shown that very often what principally drives the medication count in these cohorts of patients has been the rising number of drugs prescribed to manage, sometimes, inevitable complications (such as portal hypertension and its sequelae, sub-acute bacterial peritonitis, and portal hypertensive gastropathy, etc) that accompany decompensation in these patients. [5,25] However, devising intervention strategies aimed at both the identification and reduction of the risks and consequences of polypharmacy in this vulnerable population will require an unambiguous risk-stratification tool.…”
Section: Discussionmentioning
confidence: 99%
“…We defined polypharmacy as 5 or more medications because this threshold has been associated with poor treatment outcomes (e.g., disability, falls, frailty, and death) [ 20 ]. Furthermore, the definition has been used in most studies conducted among PWHIV to assess polypharmacy [ 21 ]. We assessed the pharmacologically active ingredients rather than the number of pills because the former is more comprehensive and can capture whether nonadherence to ART is due to pill burden or drug unintended effects.…”
Section: Methodsmentioning
confidence: 99%
“…Polypharmacy is defined as the concomitant use of multiple (five or more) medications by an individual (Danjuma et al, 2022). In a study of 1258 PLWH with a mean age of 72 (SD = 4.27) years for male participants and a mean age of 71 (SD = 3.94) years for females, Guaraldi et al (2018) reported polypharmacy and multimorbidity increased with the length of time that participants had lived with HIV.…”
Section: Polypharmacy and Drug Effectsmentioning
confidence: 99%